Potentiation of human immunodeficiency virus type 1 Tat by human cellular proteins. - Greenberg, M E (1997)
The Tat protein is a potent activator of human immunodeficiency virus type 1 transcription. Tat has been shown to act by increasing both transcription initiation and elongation, but a detailed understanding of its interaction with the transcriptional machinery is lacking. With the aim of isolating cellular proteins that interact with Tat and play a role in transactivation, we have reexamined its function in a cell-free transcription assay. Monitoring the appearance of transactivation after addition of purified Tat at intervals to the reaction mix revealed a lag of approximately 10 min before Tat is able to effect transactivation. Incubation of Tat in nuclear or cytoplasmic extracts of human cells was sufficient to eliminate the lag, but nuclear extract from a rodent cell line was inactive. The accelerating effect of the human cell extract could be abrogated by dilution, heat inactivation, or chromatographic depletion. We infer that Tat is potentiated for transactivation through interaction with a protein factor(s) that is specific to human cells.